Sing to Victory! : Song in Soviet Society During World War II. - Ament, Suzanne (Academic Studies Press, 2019)
This well researched, multi-faceted book depicts the relationship between song and society during WWII in the USSR. The songs from that era created a true cultural legacy which reflected both the hearts of the individuals fighting and the narrative of the party and state in bringing the nation to victory.